2013
DOI: 10.1590/s1414-462x2013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional de pré-escolares de creche pública: um estudo longitudinal

Abstract: ResumoO objetivo do estudo foi monitorar o estado nutricional de pré-escolares de uma creche pública. Trata-se de um estudo longitudinal, antes (t 0 ) e depois (t 1 ), com 51 crianças de 2 a 4 anos de idade. Os procedimentos foram: avaliação antropométrica (P/I, P/E e E/I -OMS 2006, classificação SISVAN-2008); avaliação bioquímica (colesterol total, HDLc, LDLc, triglicerídeos e glicose); avaliação hematológica (hemoglobina); avaliação dietética (pesagem direta dos alimentos e registro alimentar). Para determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
3
0
8
Order By: Relevance
“…Corroborating these results, a study with children in this age group showed that children from families with an income of 2 to 3 minimum wages are twice as likely (OR 2.23, 95CI 1.34-3.72) to be overweight than those belonging to families with incomes of up to one minimum wage. 26 Therefore, income is one of the factors that could encourage the consumption of healthier foods by increasing access to such, meaning that diet may be a protective factor for overweight. However, the most appropriate choices do not depend exclusively on income but also family eating habits, level of education, and the availability of time for the preparation of food, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborating these results, a study with children in this age group showed that children from families with an income of 2 to 3 minimum wages are twice as likely (OR 2.23, 95CI 1.34-3.72) to be overweight than those belonging to families with incomes of up to one minimum wage. 26 Therefore, income is one of the factors that could encourage the consumption of healthier foods by increasing access to such, meaning that diet may be a protective factor for overweight. However, the most appropriate choices do not depend exclusively on income but also family eating habits, level of education, and the availability of time for the preparation of food, among others.…”
Section: Discussionmentioning
confidence: 99%
“…34 The relationship between attendance at the day care center and the nutritional status of preschool children has been gaining interest in the current scenario, given that the children spend most of their day at such institutions, meaning that day care centers are responsible for providing most daily meals and, consequently, the supply of nutrients. 26 In addition, these institutions no longer have merely a "supporting role" and have assumed an important function in child education, including the promotion of health actions that interfere in the nutritional status of preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, não foi possível observar diferenças estatísticas relacionadas a esses índices, considerando as mudanças ao longo dos 12 meses de estudo. Apesar de poucos estudos terem desenvolvido análises similares, considerando como população de referência o standard de crescimento estabelecido pela OMS em 2006 14 , resultados diferentes foram encontrados em outros estudos, nos quais houve variação temporal do estado nutricional favorável 16,17 . Os resultados encontrados neste estudo podem estar circunstanciados às melhorias nas condições de vida da população brasileira, explicativas do declínio da desnutrição no país 18,19 , condicionando à aproximação dos parâmetros antropométricos aos que seriam proporcionados pela plenitude do potencial genético quando superadas as condições adversas do meio ambiente.…”
Section: Discussionunclassified
“…Outros estudos que utilizaram o SISVAN [26][27][28] verificaram apenas o estado nutricional, através da análise antropométrica ou relacionado ao aleitamento materno. No caso do município de Arvorezinha, RS, o SISVAN é usado apenas para avaliar peso e altura dos beneficiários do programa Bolsa Família.…”
Section: Discussionunclassified